High photocatalytic activity of oliver-like BiVO4 for Rhodamine B degradation under visible light irradiation / Huu Vinh Nguyen, Tran Van Thuan, Sy Trung Do, Duy Trinh Nguyen, Dai-Viet N. Vo, Long Giang Bach - Tran, Van Thuan
We report the facial synthesis of BiVO4 crystals with different morphologies by the solvothermal and hydrothermal process. The phase structure and morphology as-synthesized samples were characterized by XRD, FE-SEM, and UV-vis DRS spectroscopy. We also investigated the photocatalytic activity of BiVO4 for the decomposition of rhodamine B (RhB) under visible light irradiation. The results showed that oliver-like BiVO4 was obtained when using the mixed solvent of ethylene glycol and water while starflower-like BiVO4 was obtained using the mixed solvent of ethylene glycol monomethyl ether and water. The hydrothermal evolution process the BiVO4 product with a rod-like morphology. Oliver-like BiVO4 with pure monoclinic scheelite phase and high specific surface area exhibits efficient photodegradation of RhB (k = 7.82x10-3 min-1).